1991
DOI: 10.1007/bf01954999
|View full text |Cite
|
Sign up to set email alerts
|

Small-intestinal abnormalities in cystic fibrosis patients

Abstract: A survey is given of the pathophysiology of the main alterations in the small intestine of cystic fibrosis patients. Special attention is paid to the understanding of meconium ileus in the fetus and the newborn, the repercussion of duodenal acidity on the duodenal mucosa and the intraduodenal digestion, and primary and secondary biochemical alterations in the secretory-digestive-absorptive function of the small-intestinal mucosa. The meconium equivalent syndrome and its connection with the atypical course of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 32 publications
1
25
0
Order By: Relevance
“…In contrast, CF patients were significantly more likely to have initial troughs of Յ1.5 g/ml by univariate analysis. A recently published voriconazole pharmacokinetics study among lung transplant recipients at our center identified CF as the most important patient variable associated with poor bioavailability (14, 15) likely due to intestinal mucosal dysfunction and other physiologic changes that accompany the disease (12,14,15). In another report, 50% to 70% of voriconazole troughs measured in CF patients were Յ1.5 g/ml during any given time period following lung transplantation (4).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, CF patients were significantly more likely to have initial troughs of Յ1.5 g/ml by univariate analysis. A recently published voriconazole pharmacokinetics study among lung transplant recipients at our center identified CF as the most important patient variable associated with poor bioavailability (14, 15) likely due to intestinal mucosal dysfunction and other physiologic changes that accompany the disease (12,14,15). In another report, 50% to 70% of voriconazole troughs measured in CF patients were Յ1.5 g/ml during any given time period following lung transplantation (4).…”
Section: Discussionmentioning
confidence: 99%
“…Due to its high lipophilicity and low water solubility, absorption of voriconazole is associated with digestion of fat and the subsequent formation of micelles. However, this process is severely impaired in CF patients for many reasons, including (i) pancreatic insufficiency, leading to decreased secretion of pancreatic enzymes (lipase), (ii) reduced activity of lipase due to low duodenal pH caused by decreased secretion of pancreatic bicarbonate (16) and gastric acid hypersecretion (6), (iii) precipitation of bile salts at low duodenal pH, leading to low duodenal bile salt concentration and a diminished bile salt pool (precipitated bile salts are not reabsorbed) (10), and (iv) intestinal mucosal dysfunction, alterations in the intestinal mucus layer, and accelerated intestinal transit time (8,30).…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesized origin for the reduced growth of the CF mouse is the intestine. CF mice display impaired gastrointestinal physiology since they experience a high incidence of intestinal obstruction (9,21,39,48) similar to the less frequently occurring meconium ileus and distal intestinal obstruction syndrome observed in CF patients (15). The intestinal dysfunction in CF may include intestinal mucosal defects that interfere with normal nutrient absorption, leading to reduced growth (8,38).…”
mentioning
confidence: 97%